The influence of english teachers' motivation in their teaching practices - LIMA, Mírian Celerino dos Anjos (2023)
The purpose of this article is to verify how motivated English teachers in Altamira-Pará are, also observe types of strategies that teachers applied in their teaching perform. This study may help schools and colleges to develop the motivation level of teachers to have a good performance in order to increase the educational system. The study shows abundant importance about teachers’ motivation in the field of education. The study may be beneficial for teachers that play important role in an education system. If teachers are not motivated and having low performance then they cannot give their best efforts, so, maybe if the schools give some training, orientation and support about some attitudes these could help teachers get a good results in their jobs performance.